The effects of housing density on mouse thermal physiology depend on sex and ambient temperature - Vojtěch Škop; Cuiying Xiao; Naili Liu; Oksana Gavrilova; Marc L. Reitman (Elsevier, 2021)
Objective: To improve understanding of mouse energy homeostasis and its applicability to humans, we quantitated the effects of housing density on mouse thermal physiology in both sexes. Methods: Littermate wild type and Brs3-null mice were single- or group- (three per cage) housed and studied by indirect calorimetry with continuous measurement of core body temperature, energy expenditure, physical activity, and food intake. Results: At 23 °C, below thermoneutrality, single-housed males had a lower body temperature and unchanged metabolic rate compared to group-housed controls. In contrast, single-housed females maintained a similar body temperature to group-housed controls by increasing their metabolic rate. With decreasing ambient temperature below 27 °C, only group-housed mice decreased their heat conductance, likely due to huddling, thus interfering with the energy expenditure vs ambient temperature relationship described by Scholander. In a hot environment (35 °C), the single-housed mice were less heat stressed. Upon fasting, single-housed mice had larger reductions in body temperature, with male mice having more torpor episodes of similar duration and female mice having a similar number of torpor episodes that lasted longer. Qualitatively, the effects of housing density on thermal physiology of Brs3-null mice generally mimicked the effects in controls. Conclusions: Single housing is more sensitive than group housing for detecting thermal physiology phenotypes. Single housing increases heat loss and amplifies the effects of fasting or a cold environment. Male and female mice utilize different thermoregulatory strategies to respond to single housing.